Is there an association between overweight/obesity and dental implant complications? A systematic review and meta-analysis - Monteiro, J. L. G. C.; Pellizzer, E. P. [UNESP]; Araujo Lemos, C. A. [UNESP]; Moraes, S. L. D. de; Egito Vasconcelos, B. C. do (Churchill Livingstone, 2019)
The aim of this systematic review was to test the following hypotheses: (1) that there is no difference in implant survival rate between individuals with overweight or obesity and those who are within the ideal weight range; (2) that there are no differences between these groups regarding indicators of peri-implant health. Two independent reviewers performed a literature search of the PubMed/MEDLINE, Scopus, and Cochrane Library databases for studies published up to April 1, 2018. A meta-analysis was performed to determine the risk difference for implant failure and mean difference for marginal bone loss, probing depth, and bleeding on probing. Six studies were selected for review, involving a total of 746 patients with 986 implants: 609 in overweight or obese individuals and 377 in individuals within the ideal weight range. The findings of this systematic review indicate that the first hypothesis should be accepted, since no statistically significant difference in implant survival rate was found between individuals with overweight/obesity and those within the ideal weight range (P = 0.64). The second hypothesis was rejected, as the review indicated a difference in marginal bone loss (P < 0.00001), probing depth (P < 0.00001), and bleeding around dental implants (P < 0.00001).
Keywords: obesity; dental implants; meta analysis